JOHN DEWEY'S THINKING CONSTRUCTION ON EXPERIENCE-BASED EDUCATION - Mutrofin (Journal of Education and Learning Sciences, 2022)
This report analyzes John Dewey's work on experience-based education. It's been said that the finest teacher is experienced. It might not be excessive because everyone has experience that they can use to evaluate things. When considering experience-based learning, it is crucial to remember that as people get older, have more opportunities, and reach higher levels of maturity, their experiences also get bigger and bigger. Not just a slew of experiences for the sake of having a good time, but more experience is a fusion that enriches and nourishes. John Dewey places a great emphasis on the idea that all education is acquired via experience. These encounters may be private or communal. Every encounter creates something priceless in human life